Oxytocin and olfaction - Oettl, Lars-Lennart; Kelsch, Wolfgang (Behavioral pharmacology of neuropeptides: Oxytocin, 2017)
Social signals are identified through processing in sensory systems to trigger appropriate behavioral responses. Social signals are received primarily in most mammals through the olfactory system. Individuals are recognized based on their unique blend of odorants. Such individual recognition is critical to distinguish familiar conspecifics from intruders and to recognize offspring. Social signals can also trigger stereotyped responses like mating behaviors. Specific sensory pathways for individual recognition and eliciting stereotyped responses have been identified both in the early olfactory system and its connected cortices. Oxytocin is emerging as a major state modulator of sensory processing with distinct functions in early and higher olfactory brain regions. The brain state induced through Oxytocin influences social perception. Oxytocin acting on different brain regions can promote either exploration and recognition towards same- or other-sex conspecifics, or association learning. Region-specific deletion of Oxytocin receptors suffices to disrupt these behaviors. Together, these recent insights highlight that Oxytocin’s function in social behaviors cannot be understood without considering its actions on sensory processing.